Evaluasi Program Pembinaan Latihan Pencak Silat di UKM PSHT UNESA - M. Farid Putra; Heri Wahyudi; Shidqi Hamdi Pratama Putera; Muhammad Dzul Fikri (MAN Insan Cendekia Jambi, 2026)
Sports development programs in higher education institutions have distinct characteristics compared to professional clubs or training centers, thus requiring systematic and contextual program evaluation. The Persaudaraan Setia Hati Terate (PSHT) Student Activity Unit at Universitas Negeri Surabaya plays a strategic role in developing students’ achievements in pencak silat. However, the effectiveness of the implemented training program needs to be examined empirically to ensure program quality and sustainability. This study aimed to evaluate the pencak silat training development program of the PSHT Student Activity Unit at Universitas Negeri Surabaya using the CIPP evaluation model (Context, Input, Process, Product). A descriptive evaluative approach was employed. Data were collected through questionnaires administered to 30 athletes, one coach, and one student organization leader as key informants, and were complemented by interviews. Quantitative descriptive analysis was applied to questionnaire data and reinforced by qualitative analysis of interview results. The findings indicate that, overall, the PSHT training development program at Universitas Negeri Surabaya was categorized as very good. The context and process components achieved very good ratings, reflecting clear program objectives and effective training implementation. Meanwhile, the input and product components were rated as good, indicating that resources and performance outcomes supported the program, although further optimization is required. These findings confirm the effectiveness of the CIPP model as an evaluation tool for sports development programs in higher education settings.